Describing Pictures in Improving the Students’ Ability in Writing - Hariadi Syam; Rais Abin (Universitas Negeri Makassar, 2019)
This Research was designed to improve the students’ ability in writing by Describing pictures.The problem of the research was “can describing pictures improve students’ ability in writing?”. There were many kinds of strategies that could be used in teaching writing, but in this research, the researcher applied only describing pictures, and writing activities focusing on the kinds of activities. The design of this research was Collaborative Classroom Action Research (CAR). Based on the analytical scoring rubric showed that from 63 in the first cycle and got increased to 73 in the second cycle. In the first cycle there were 13 Students of 30 students could reach the minimum score or only 43 % students were success. While in the last cycle there were 27 Students of 30 students could reach even greater that the minimum score or 90% students were success.Based on the conclusion of this research the researcher suggests some points. Firstly, describing pictures could be employed to improve the students’ ability in writing. Secondly, it was suggested that the English teacher could apply describing pictures as one of the alternative techniques that could be used in the teaching of English to all skills especially writing.